Acute Ethanol Produces Ataxia and Induces Fmr1 Expression via Histone Modifications in the Rat Cerebellum. (14th May 2019) - Dulman, Russell S.; Auta, James; Teppen, Tara; Pandey, Subhash C.
Abstract : Background: The cerebellum is fundamental for motor coordination and therefore crucial in ethanol (EtOH)‐induced ataxia. EtOH contributes to cerebellar pathophysiology. Fragile‐X mental retardation protein (FMRP) is a complex regulator of RNA and synaptic plasticity implicated in fragile‐X tremor and ataxia syndrome, a phenotype featuring increased Fmr1 mRNA expression. Recent studies have implicated glutamatergic targets of FMRP in hereditary cerebellar ataxias including the main cerebellar excitatory amino acid ( Eaa1 ) transporter and a subtype of metabotropic glutamate receptor ( Grm5 ). However, EtOH‐induced changes in cerebellar Fmr1 expression and its epigenetic regulation have not been investigated. Here, we examined the effects of acute EtOH exposure on ataxic behavior, gene expression, and epigenetic regulation of the Fmr1 gene and its glutamatergic targets in the rat cerebellum. Methods: Male adult Sprague Dawley rats received acute EtOH (2 g/kg) intraperitoneally 1 hour prior to ataxic behavioral testing on the accelerating rotarod and were sacrificed immediately thereafter. Cerebellar tissues were analyzed for gene expression and epigenetic regulation of the Fmr1 gene and its glutamatergic targets in the rat cerebellum using real‐time quantitative polymerase chain reaction (PCR) and chromatin immunoprecipitation. Results: Acute EtOH exposure caused marked ataxia on the accelerating rotarod test compared with saline‐treated controls. This ataxic response was associated with increases in mRNA levels of Fmr1, postsynaptic density 95 (Psd95), Eaa1, and Grm5 in the cerebellum. In addition, we found increased H3K27 acetylation both at the promoter region of Fmr1 and at a proposed cyclic adenosine monophosphate (cAMP) response‐element binding (CREB) site downstream of the Fmr1 transcription start site. Furthermore, acute EtOH exposure significantly increased Creb1 and the histone acetyltransferases (HAT) CREB binding protein ( Cbp ), and p300 mRNA transcripts. Conclusions: Overall, EtOH regulates cerebellar Fmr1 expression most likely via HAT‐mediated increase in histone acetylation. We propose that FMRP regulation of glutamatergic transcripts plays an important role in disrupting the excitatory–inhibitory balance in the cerebellum underlying EtOH‐induced ataxia. Abstract : The cerebellum plays an important role in ethanol‐induced ataxia. We assessed acute ethanol's effect on motor behavior, gene expression, and epigenetic regulation of the Fmr1 gene and its RNA‐binding targets in rat cerebellum. Ethanol produced marked ataxia associated with increased cerebellar mRNA levels of Fmr1 and associated target genes, as well as histone H3K27acetylation of Fmr1 gene. We propose that epigenetic regulation of Fmr1 modulates expression of glutamatergic transcripts in the cerebellum possibly contributing to ataxia, as represented in model.